Utilization of steam-flaked milo or corn and supplemental fat by finishing steers - Brandt, Robert T., Jr.; Kuhl, Gerry L.; Freeman, A.S.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
One hundred forty crossbred yearling steers (815 lb) were utilized to evaluate grain type (steam flaked com vs steam flaked milo) and supplemental fat (O or 4% yellow grease) on finishing performance. There were no differences in carcass-adjusted average daily gain, feed intake, or feed conversion between steers fed milo vs com. Calculated NEtn and NEg contents of flaked milo were approximately 99% those of flaked com and 15 to 20% greater than those of dry rolled milo (NRC, 1984). Supplemental yellow grease increased (P=.12) average daily gain 4.4% and improved (P<.05) feed efficiency 6%. There were no grain type x fat interactions for any performance parameter measured. Steers fed milo had smaller (P<.05) ribeye areas and tended to have more baclcfat and internal (KPH) fat than com-fed steers. As a result, milo-fed steers had a higher (P<.OOI) yield grade. Steers fed com had a higher (P<.OOI) degree of yellow pigmentation in external fat than those fed milo. Supplemental yellow grease resulted in an additive increase (P<.025) in yellow pigmentation. There were no differences in peak shear force or sensory traits of beef longissimus muscle as a result of either grain type or fat level. Our data indicate that steam flaking can increase the net energy value of milo to nearly that of flaked com, with no detrimental effects on the quality of beef produced.
Keywords: Beef; Steam-flaking; Milo; Corn; Fat; Finishing; Carcass traits